High Resolution Satellite Data for Land Use/Land Cover Mapping - A Case Study of Bilara Tehsil, Jodhpur District - Gaur, Mahesh Kumar; Moharana, P C; Pandey, C B; Chouhan, J S; Goyal, Prachi (Annals of Arid Zone, 2016)
The availability of high-resolution Indian satellite data from IRS P-6 LISS-IV has made a significant impact on the mapping potential of natural and man-made resources. Land use and land cover change has become a central component in current strategies for managing natural resources and monitoring anthropogenic changes in the arid western Rajasthan. High-precision land-use land-cover GIS mapping was carried out using IRS-P6 LISS-IV-MX data of 2011-12 and information was also generated on existing land use/land cover with their spatial distribution. The main objectives of the present study was to interpret satellite data for land use/land cover mapping and to generate geo-database in GIS format. Ground truthing was also conducted to verify the doubtful features in the satellite image. Major land use/land cover classes identified in this area were crop land, forests and plantation, wastelands, drainage, rural and urban settlements and water body. The study area consist 1451.89 km2 lands and out of which 82.30% area under agriculture land use and only 2.55%, 0.27% and 4.76% were taken up by the built up land (including hamlets, urban and rural areas), forest and grassland and grazing land respectively. The study concluded that the LISS-IV is a better source of data for natural resource mapping over commonly used satellite imagery and can serve the diverse application of needs of the user communities. This study not only provides the high-resolution land-use maps for Bilara tehsil, but it also yields accurate area estimates of different land-use types, in particular with grassland, and crop land. This enables analysis of potential land availability and suitability for biomass production and other sustainable land uses. Key words: high resolution multispectral satellite data, land use/land cover mapping, GIS format, ground trothing.